2003
DOI: 10.1038/sj.modpathol.3800031
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase expression in low-grade endometrial stromal sarcomas: an immunohistochemical study

Abstract: Aromatase expression has been described in stromal cells of endometriosis, adenomyosis and endometrial cancer. We analyzed aromatase expression in a series of 23 low-grade endometrial stromal sarcomas. Archival formalin-fixed and paraffin-embedded material was analyzed with immunohistochemistry. Aromatase expression was evaluated with a monoclonal and a polyclonal antibody using the peroxidase-antiperoxidase method. A score was calculated based on the percentage of positive tumor cells and the staining intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Reich et al. found a high percentage of aromatase expression positivity in patients with LG-ESS, implying that aromatase inhibitors (e.g., letrozole) may play a role in the treatment of LG-ESS ( 25 ). Another study comparing aromatase inhibitors with progestins for LG-ESS treatment indicated that aromatase inhibitors were superior to progestins because of longer recurrence-free survival and fewer side effects in patients with stage II–IV disease; this, however, is not consistent with our observations ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reich et al. found a high percentage of aromatase expression positivity in patients with LG-ESS, implying that aromatase inhibitors (e.g., letrozole) may play a role in the treatment of LG-ESS ( 25 ). Another study comparing aromatase inhibitors with progestins for LG-ESS treatment indicated that aromatase inhibitors were superior to progestins because of longer recurrence-free survival and fewer side effects in patients with stage II–IV disease; this, however, is not consistent with our observations ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most ESS express aromatases [32]. Their expression is associated with tumor growth and may also be relevant to the high recurrence rate [32]. The tumors also sometimes express gonadotrophin-releasing hormone (GnRH) receptors [18].…”
Section: Pathologymentioning
confidence: 99%
“…Reich et al [31 ]noted high levels of expression of estrogen and progesterone receptors in 71 and 95% of cases, respectively. Most ESS express aromatases [32]. Their expression is associated with tumor growth and may also be relevant to the high recurrence rate [32].…”
Section: Pathologymentioning
confidence: 99%
“…Almost 80% of ESS express estrogen (ER) and progesterone receptors (PgR). Moreover, in most cases of ESS, the intratumoral immunohistochemical expression of gonadotropin releasing hormone receptor (GnRH-R) as well as androgen receptor (AR) and aromatase was demonstrated [4,5]. The predictive value of these markers has not been determined to date.…”
Section: Introductionmentioning
confidence: 99%